A second course in computer science with PASCAL - McCracken, Daniel D. (New York : John Wiley & Sons, 1987)
This is an introductory text on the central subject of computer science - the theory, implementation, and applications of data structures and algorithms.
1. the Program Development Process -- 2. Arrays and Records -- 3. Sets and String -- 4. Stacks and Queues -- 5. Recursion -- 6. Linked Lists -- 7. Trees -- 8. Sorting -- 9. Searching -- 10. Graphs.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)